Convalescent plasma therapy in patients with COVID-19. (February 2021) - Altuntas, Fevzi; Ata, Naim; Yigenoglu, Tugce Nur; Bascı, Semih; Dal, Mehmet Sinan; Korkmaz, Serdal; Namdaroglu, Sinem; Basturk, Abdulkadir; Hacıbekiroglu, Tuba; Dogu, Mehmet Hilmi; Berber, İlhami; Dal, Kursat; et al.
Abstract: Introduction: Passive antibody therapy has been used to immunize vulnerable people against infectious agents. In this study, we aim to investigate the efficacy of convalescent plasma (CP) in the treatment of severe and critically ill patients diagnosed with COVID-19. Method: The data of severe or critically ill COVID-19 patients who received anti-SARS-CoV-2 antibody-containing CP along with the antiviral treatment (n = 888) and an age-gender, comorbidity, and other COVID-19 treatments matched severe or critically ill COVID-19 patients at 1:1 ratio (n = 888) were analyzed retrospectively. Results: Duration in the intensive care unit (ICU), the rate of mechanical ventilation (MV) support and vasopressor support were lower in CP group compared with the control group (p = 0.001, p = 0.02, p = 0.001, respectively). The case fatality rate (CFR) was 24.7 % in the CP group, and it was 27.7 % in the control group. Administration of CP 20 days after the COVID-19 diagnosis or COVID-19 related symptoms were associated with a higher rate of MV support compared with the first 3 interval groups (≤5 days, 6−10 days, 11−15 days) (p=0.001). Conclusion: CP therapy seems to be effective for a better course of COVID-19 in severe and critically ill patients.